Archive Roles in Local Leaders Election: A Case Study of Election Offences - Rachmaji, Achmad Syarif (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
In 2020, the Simultaneous General Elections were held in many parts of Indonesia even during the Covid-19 outbreak. However, election offenses still occurred and even resulted in a new offense, which was the health protocols offense. The election offense records can be used as an indicator of democracy quality, besides its other roles. This paper will describe the role of archives related to election offenses. The study found that during the simultaneous election, the majority of offenses that occurred were administrative, code of ethics, criminal, and health protocols. The election offenses documents, in the archive context, become an important archive that is part of the election archive and can be grouped into types of election offenses archives, namely: health protocol offense archives, administrative offense archives, code of ethics offense archives, and criminal offenses archives. In addition, the archives can also be useful in the context of compiling infographic materials, comparison data, election policy, and mapping materials for better elections.